2021
DOI: 10.1038/s41598-021-81905-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of epidermal growth factor immobilization on 3D biocompatible scaffolds to promote tissue repair and regeneration

Abstract: Exogenous application of human epidermal growth factor (hEGF) stimulates epidermal wound healing. The aim of this study was to develop bioconjugates based on hEGF mimicking the protein in its native state and thus suitable for tissue engineering applications, in particular for treating skin-related disorders as burns. Ribonuclease A (RNase A) was used to investigate a number of different activated-agarose carriers: cyanogen bromide (CNBr)-activated-agarose and glyoxyl-agarose showed to preserve the appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Gothelf and collaborators demonstrated that the CM derived from neurotrophic factor-secreting MSCs was enriched with BDNF, VEGF-A, and HGF and has been used effectively to have protective effects in several animal models of neurodegenerative diseases [68]. EGF stimulates the growth of numerous epidermal and epithelial tissues [69], and activation of TGF-β is also involved in the recruitment of stem/progenitor cells in tissue regeneration/remodeling processes [70]. Furthermore, it has been proven that LIF, which plays a crucial role in blastocyst implantation, is able to regulate some regenerative processes after injury in several tissues [71].…”
Section: Discussionmentioning
confidence: 99%
“…Gothelf and collaborators demonstrated that the CM derived from neurotrophic factor-secreting MSCs was enriched with BDNF, VEGF-A, and HGF and has been used effectively to have protective effects in several animal models of neurodegenerative diseases [68]. EGF stimulates the growth of numerous epidermal and epithelial tissues [69], and activation of TGF-β is also involved in the recruitment of stem/progenitor cells in tissue regeneration/remodeling processes [70]. Furthermore, it has been proven that LIF, which plays a crucial role in blastocyst implantation, is able to regulate some regenerative processes after injury in several tissues [71].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, scaffold stiffness and geometry are important features to be considered, with square pores being more efficient in promoting cell adhesion rather than hexagonal pores [ 32 ]. Moreover, biochemical cues, such as growth factors [ 33 ], cytokines, and adhesion molecules, should be inserted to induce effective maturation of cardiac cells [ 21 ]. Finally, in order to produce the optimal material for tissue interfaces, the design of the cardiac biomaterial should fit with the complex electrical pathways of the myocardium [ 34 ], obtained by a fine coordination between membrane potential depolarization, pacemaker conduction system, and specific intracellular communication networks [ 35 ].…”
Section: Biomaterials For Cardiac Regenerationmentioning
confidence: 99%
“…10,11 Covalent conjugation also typically results in negligible GF release and is not ideally suited for applications where GFs internalization is required for cells to exert their intended biological effects. 60,61 In summary, extant modes of GF incorporation and delivery from electrospun meshes suffer from several limitations such as the use of additional processing steps, promotion of sharp burst release profiles for surface-adsorbed proteins, direct coupling of GF release kinetics with intrinsic fiber properties for blend electrospun meshes, potential loss of GF conformation-activity, significantly delayed release from coaxially prepared core−shell meshes, and possible negative impact on bulk mesh properties.…”
Section: Conventional Modes Of Growth Factormentioning
confidence: 99%
“…While covalent conjugation avoids exposure of GFs to electrospinning conditions, it can potentially interfere with GF activity should access to the binding epitope be reduced during the conjugation step. Moreover, most synthetic polymers used for electrospinning often lack active sites for direct covalent conjugation; therefore, additional surface treatments or the inclusion of natural polymers is required prior to protein immobilization. , Covalent conjugation also typically results in negligible GF release and is not ideally suited for applications where GFs internalization is required for cells to exert their intended biological effects. , …”
Section: Conventional Modes Of Growth Factor Delivery From Electrospu...mentioning
confidence: 99%